Placental SLC38A4 gene polymorphisms 1304 G > A and 292 C > T, and their association with glucose > 95 mg/dl in normal weight full-term healthy newborns - Carlos Galaviz-Hernández; Martha Sosa-Macías; Martha Rodríguez-Morán; Gerardo Martínez-Aguilar; Fernando Guerrero-Romero; Siblie M. González-Rentería (Boletín Médico del Hospital Infantil de México, 2021)
Background: The SLC38A4 gene encodes for the SNAT4 protein, which has been related to glucose metabolic alterations in human newborns. This study aimed to determine whether the 1304 G > A and 292 C > T polymorphisms of the SLC38A4 gene are associated with the presence of glucose levels > 95 mg/dL in normal weight full-term healthy newborns. Methods: We conducted a case–control study and analyzed 50 normal weight full-term healthy newborns. Groups were defined based on glucose levels: > 95 mg/dL (cases; n = 13) and < 95 mg/dL (controls; n = 37). The 1304 G > A and 292 C > T polymorphisms of the SLC38A4 gene were determined through quantitative polymerase chain reaction using placental DNA. The association between polymorphism and glucose levels > 95 mg/dL was established using multivariate logistic regression analysis. Results: No significant differences were observed either for gestational age or body weight at birth between groups. In the case group, newborns showed significantly higher homeostatic model assessment for insulin resistance than those in the control group (p < 0.0005). The odds ratio (OR) between the SLC38A4 gene 292 C > T single-nucleotide polymorphism (SNP) and glucose levels > 95 mg/dL was 7.78 (p = 0.024), whereas no significant association was found for the 1304 G > A SNP (OR 1.46; p = 0.77). Conclusions: Our results suggest that the SLC38A4 gene 292 C > T SNP is associated with glucose levels > 95 mg/dL in normal weight full-term healthy newborns.